2017
DOI: 10.1108/jbim-01-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

Business streamlining – an integrated model of service sourcing

Abstract: Purpose The purchasing of services is a significantly under-researched area. The purpose of this study is to suggest a conceptual model of service sourcing relationships, including the post-contract phase. Design/methodology/approach A qualitative methodology involving two longitudinal case studies that were analyzed with a grounded theory approach to build a conceptual model was applied. Findings The proposed model consists of a core process that is termed “business streamlining” and denotes the process b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 57 publications
(101 reference statements)
5
19
0
Order By: Relevance
“…Finally, by collating the research areas studied in the supply literature and the SLR results, further directions for future research are identified. Procurement of services requires further investigation; this finding is also supported by Kleemann and Essig (2013) and Molin and Åge (2017). Indeed, the SLR revealed a low proportion of relevant articles compared to the total number of identified articles and the fragmented nature of the literature, with a lack of studies focusing on each specific topic.…”
Section: Discussion and Directions For Future Research Developmentsupporting
confidence: 56%
See 3 more Smart Citations
“…Finally, by collating the research areas studied in the supply literature and the SLR results, further directions for future research are identified. Procurement of services requires further investigation; this finding is also supported by Kleemann and Essig (2013) and Molin and Åge (2017). Indeed, the SLR revealed a low proportion of relevant articles compared to the total number of identified articles and the fragmented nature of the literature, with a lack of studies focusing on each specific topic.…”
Section: Discussion and Directions For Future Research Developmentsupporting
confidence: 56%
“…Finally, by collating the research areas studied in the supply literature and the SLR results, further directions for future research are identified. Procurement of services requires further investigation; this finding is also supported by Kleemann and Essig (2013) and Molin and Åge (2017). Indeed, the SLR revealed a low proportion of • Potentially negative outcomes from VCC resulting from role conflicts and ambiguity, opportunism and power plays (Chowdhury et al, 2016) • Impact of customer involvement on the ability of the provider to fulfil its tasks (Nullmeier et al, 2016)…”
Section: Discussion and Directions For Future Research Developmentmentioning
confidence: 64%
See 2 more Smart Citations
“…The goal of this research was to develop a deeper understanding of the quality evaluation process in project-based consulting assignments and provide a universal framework for defining the main factors of perceived quality. Concerning the grounded theory approach, it is not free of distortions and uncertainties but not unprecedented in the B2B research practice either (Cova et al , 2019; Molin and Åge, 2017). The study relied on interviews from 22 participants of 14 different organizations and the results reflect the participants’ subjective perceptions about the quality of consulting projects.…”
Section: Limitations and Future Researchmentioning
confidence: 99%